Endothelial progenitor cells transplantation attenuated blood-brain barrier damage after ischemia in diabetic mice via HIF-1α - Jieli Geng; Liping Wang; Meijie Qu; Yaying Song; Xiaojie Lin; Yajing Chen; Muyassar Mamtilahun; Shengdi Chen; Zhijun Zhang; Yongting Wang; Guo-Yuan Yang (Stem Cell Research & Therapy, 2017)
Abstract Background Blood-brain barrier impairment is a major indicator of endothelial dysfunction in diabetes. Studies showed that endothelial progenitor cell (EPC) transplantation promoted angiogenesis and improved function recovery after hind limb ischemia in diabetic mice. The effect of EPC transplantation on blood-brain barrier integrity after cerebral ischemia in diabetic animals is unknown. The aim of this study is to explore the effect of EPC transplantation on the integrity of the blood-brain barrier after cerebral ischemia in diabetic mice. Methods EPCs were isolated by density gradient centrifugation and characterized by flow cytometry and immunostaining. Diabetes was induced in adult male C57BL/6 mice by a single injection of streptozotocin at 4 weeks before surgery. Diabetic mice underwent 90-minute transient middle cerebral artery occlusion surgery and received 1 × 106 EPCs transplantation immediately after reperfusion. Brain infarct volume, blood-brain barrier permeability, tight junction protein expression, and hypoxia inducible factor-1α (HIF-1α) mRNA level were examined after treatment. Results We demonstrated that neurological deficits were attenuated and brain infarct volume was reduced in EPC-transplanted diabetic mice after transient cerebral ischemia compared to the controls (p < 0.05). Blood-brain barrier leakage and tight junction protein degradation were reduced in EPC-transplanted mice (p <0.05). EPCs upregulated HIF-1α expression while HIF-1α inhibitor PX-478 abolished the beneficial effect of EPCs. Conclusions We conclude that EPCs protected blood-brain barrier integrity after focal ischemia in diabetic mice through upregulation of HIF-1α signaling.